Effect of biomechanical stress on endogenous antioxidant networks in bovine articular cartilage. Issue 2 (17th October 2017) - Issa, Rita; Boeving, Michael; Kinter, Michael; Griffin, Timothy M.
ABSTRACT: Mechanosensitve pathways in chondrocytes are essential for maintaining articular cartilage homeostasis. Traumatic loading increases cartilage oxidation and causes cell death and osteoarthritis. However, sub‐lethal doses of the pro‐oxidant molecule tert‐Butyl hydroperoxide (tBHP) protects against loading‐induced chondrocyte death. We hypothesized that compressive cyclic loading at moderate strains (<20%) causes sub‐lethal cartilage oxidation that induces an adaptive increase in the endogenous antioxidant defense network. We tested this hypothesis by subjecting healthy bovine articular cartilage explants to in vitro static or cyclic (1 Hz) compressive loading at 50 kPa (15% strain, "physiologic") versus 300 kPa (40% strain, "hyper‐physiologic") for 12 h per day for 2 days. We also treated unloaded explants with 100 μM tBHP for 12 h per day for 2 days to differentiate between biomechanical and chemical pro‐oxidant stimulation. All loading conditions induced glutathione oxidation relative to unloaded controls, but only the 50 kPa cyclic loading condition increased total glutathione content (twofold). This increase was associated with a greater expression of glutamate‐cysteine ligase, the rate‐limiting step in glutathione synthesis, compared to 300 kPa cyclic loading. 50 kPa cyclic loading also increased the expression of superoxide dismutase‐1 and peroxiredoxin‐3. Like 50 kPa loading, tBHP treatment also increased total glutathione content. However, tBHP treatment and 50 kPa cyclic loading differed in their effect on the expression of genes regulating antioxidant defense and cartilage matrix synthesis and degradation. These findings suggest that glutathione metabolism is a mechanosensitive antioxidant defense pathway in chondrocytes and that intermittent pro‐oxidant treatment alone is insufficient to account for all changes in mediators of cartilage homeostasis associated with cyclic loading. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:760–769, 2018.